2007
DOI: 10.1016/j.jacc.2007.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Olmesartan, But Not Amlodipine, Improves Endothelium-Dependent Coronary Dilation in Hypertensive Patients

Abstract: Olmesartan, but not amlodipine, improved endothelium-dependent coronary dilation in hypertensive patients independent of BP reduction. These beneficial effects on coronary vasomotion might be via an antioxidant property of ARBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 16 publications
8
51
1
Order By: Relevance
“…Interestingly, we found that changes in pre-and post-heparin EC-SOD levels after olmesartan treatment were significantly and positively correlated with those in FMD, indicating the possibility that olmesartan may improve FMD by increasing EC-SOD to some degree, though these changes did not translate into overall changes in pre-and post-heparin EC-SOD levels. These observations are similar to those reported by Naya et al 36 who found that olmesartan, but not amlodipine, improved endothelium-dependent coronary dilation in hypertensive patients and there was a significant correlation between the changes in endothelial function and SOD levels. Deterioration in renal function, namely chronic kidney disease, is associated with increased cardiovascular morbidity and mortality in the general population and various patient settings.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, we found that changes in pre-and post-heparin EC-SOD levels after olmesartan treatment were significantly and positively correlated with those in FMD, indicating the possibility that olmesartan may improve FMD by increasing EC-SOD to some degree, though these changes did not translate into overall changes in pre-and post-heparin EC-SOD levels. These observations are similar to those reported by Naya et al 36 who found that olmesartan, but not amlodipine, improved endothelium-dependent coronary dilation in hypertensive patients and there was a significant correlation between the changes in endothelial function and SOD levels. Deterioration in renal function, namely chronic kidney disease, is associated with increased cardiovascular morbidity and mortality in the general population and various patient settings.…”
Section: Discussionsupporting
confidence: 92%
“…These beneficial effects on coronary & forearm vasomotion might be via an antioxidant property of ARBs. [16,17] In this study, olmesartan an angiotensin receptor antagonist showed significant and consistent free radical scavenging activity by DPPH and Nitric oxide radical scavenging assays.Free radical scavenging activity of calcium channel blocker amlodipine was more significant than olmesartan but was inconsistent and non-concentration dependent.…”
Section: Discussionsupporting
confidence: 51%
“…Participants were instructed to fast for > 6h, and to abstain from caffeine-containing products for > 24 hours prior to PET studies [4,[25][26]. Smokers were also instructed to refrain from smoking for >12h before the PET studies.…”
Section: Pet Acquisition Protocolmentioning
confidence: 99%
“…Coronary endothelial dysfunction is the earliest abnormality in the development of coronary atherosclerosis and is also independently associated with future cardiac events [2]. Several coronary risk factors adversely affect endothelial function [3][4][5][6]. Among these risk factors, smoking is the leading cause of preventable cardiovascular death and is a related factor in more than 450,000 deaths annually in the United States [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation